catena-Poly[[tris(4-fluorobenzyl)tin(IV)]{mu-[(N,N-diisopropylcar bamothioyl)sulfanyl]acetato-kappa O-2:O `}] - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, [Sn(C7H6F)(3)(C9H16NO2S2)](n), the Sn atom is coordinated in a slightly distorted, trans-C3SnO2 trigonal-bipyramidal environment. Symmetry-related Sn atoms are bridged by diisopropyldithiocarbamoylacetato ligands, forming a one-dimensional polymer along [001].